3) probably because it is set up for substitution.
C works in the first equation, but check it in the second equation. I don't think it works there.
2x + 3(-3x) = 6
2x -6x = 6
can you finish if from here. make sure the answer works in both equations.
3. What would be the simplest way to solve the system?
y=1/2x
2x + 3y = 28
A. Graphing
B. Substitution***** MY ANSWER!
C. Elimination
D. Distributive
4. What is the solution of the system?
y=-3x
2x + 3y = 6
A. (2,6)
B. (-1,3)
C. (-2,6)*****MY ANSWER!
D. (1.5, -4.5)
Please help, and if you have any other answers, please tell me! :)
3 answers
John1 meant to say 3(-3x) = -9x , not -6x
then 2x - 9x = 6
-7x = 6
x = -6/7 ---> not found in any of the answers, so I suspect a typo somewhere
y = -3(-6/7) = 18/7
(-6/6 , 18/7) is the correct solution
This answer works in both equations
then 2x - 9x = 6
-7x = 6
x = -6/7 ---> not found in any of the answers, so I suspect a typo somewhere
y = -3(-6/7) = 18/7
(-6/6 , 18/7) is the correct solution
This answer works in both equations
You'll are all wrong!!! The correct answer to #7 is (B.) Substitution and the correct answer to #8 are (C.) (-2,6).
And Reiny... you didn't make any sense and the "answer" you gave wasn't even an option.
And Reiny... you didn't make any sense and the "answer" you gave wasn't even an option.